2022
DOI: 10.3389/fphar.2022.871492
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Pharmacokinetics/Pharmacodynamics, and Absolute Bioavailability of Dexmedetomidine Hydrochloride Nasal Spray in Healthy Subjects: A Randomized, Parallel, Escalating Dose Study

Abstract: Background: The present study evaluated the safety, pharmacokinetics/pharmacodynamics (PK/PD), and absolute bioavailability (Fabs) of Dex nasal spray in healthy adult subjects, which serves as a bridge for the subsequent study in children.Methods: Part 1: a double-blind, placebo-controlled, single ascending dose study was performed on 48 subjects. For 20-/40-μg groups, every 6/2 subjects received either Dex/placebo nasal spray or Dex/placebo injection in two periods. In total, 12/4 subjects each received 100 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The reason may be related to the drug action and administration method of dexmedetomidine. On the one hand, dexmedetomidine has a certain analgesic effect, reducing pain induced hypertension in patients; On the other hand, dexmedetomidine administered through the nasal cavity has a slow onset rate and avoids adverse reactions such as blood pressure drop and bradycardia caused by intravenous injection [ 30 ]. Dexmedetomidine has a better postoperative sedative and analgesic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The reason may be related to the drug action and administration method of dexmedetomidine. On the one hand, dexmedetomidine has a certain analgesic effect, reducing pain induced hypertension in patients; On the other hand, dexmedetomidine administered through the nasal cavity has a slow onset rate and avoids adverse reactions such as blood pressure drop and bradycardia caused by intravenous injection [ 30 ]. Dexmedetomidine has a better postoperative sedative and analgesic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The doses were safe and effective. Using the optimized nasal spray method can greatly improve the bioavailability of the test drug in healthy adults [ 25 ]. Intranasal administration of 1.0 μg/kg dexmedetomidine is reportedly more effective than buccal administration of 1.0 μg/kg dexmedetomidine for premedication in children [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…By producing ne small particles, the spray is expected to have less drug loss, increased bioavailability, and improved compatibility as compared with drops [14]. Previous studies demonstrated that the bioavailability of dexmedetomidine nasal spray was higher than that of nasal drops [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…This nasal spray was administered directly with no need of dilution or con guration before use. We previously evaluated its safety and tolerability, pharmacokinetics, and pharmacodynamics in healthy adults [15] and children undergoing elective surgery under general anaesthesia (NCT04200235). Its effectiveness and favorable safety pro le have been demonstrated in the adult pre-anaesthetic sedation setting in a pivotal phase 3 study (NCT04383418).…”
Section: Introductionmentioning
confidence: 99%